m-convex functions of higher order - Lara, Teodoro; Merentes, Nelson; Rosales, Edgar (Annales Mathematicae Silesianae, 2019)
In this research we introduce the concept of m-convex function of higher order by means of the so called m-divided difference; elementary properties of this type of functions are exhibited and some examples are provided.